Object Illusion Reality : Contemporary American Photography. - Cowin, Eileen; Curran, Darryl; Faulds, W. Rod (Los Angeles : California State University - Fullerton Art gallery, 1981)
Hammerbeck, Wanda ; Gleber, Conrad ; Mock, Stanley ; Brown, Bob ; Granirer, Martus ; Bowers, Harry ; Pfahl, John ; Rice, Leland ; Freeman, Vida ; Parker, Bart ; Cortright, Steven ; Hugunin, James R.
Object Illusion Reality : Contemporary American Photography, California State University - Fullerton Art gallery, Fullerton, September 21 - October 18, 1979 ; Gemeentelijk Van Reekummuseum, Apeldoorn, 13.2. t/m 14.3.1982
Engels
boek